Legal Reconstruction of Non-Conviction-Based Asset Forfeiture for State Loss Recovery from Corruption Crimes - Adhitya Anugrah Nasution; Riswadi Riswadi (Return : Study of Management, Economic and Bussines, 2024)
The confiscation of assets without criminal prosecution has become a crucial mechanism in the fight against corruption in Indonesia, particularly in cases where prosecution is hindered by the death or absence of the perpetrators. Despite being permitted under Law Number 31 of 1999 in conjunction with Law Number 20 of 2001, its implementation faces significant challenges, primarily stemming from legal uncertainty and gaps in regulatory frameworks. This study aims to address these issues by examining the existing regulations, identifying deficiencies, and proposing legal reforms to enhance asset recovery mechanisms. Utilizing a normative method approach, this study analyzes national regulations and compares them with international practices, particularly those outlined in the United Nations Convention Against Corruption (UNCAC) 2003. The results highlight that the current laws lack clarity and comprehensiveness, leading to inconsistent application and difficulties in recovering state assets. The study recommends legal reconstruction, including amendments and additions to existing laws, to bridge these gaps. By adopting international best practices, Indonesia can improve its legal framework, ensuring more effective asset recovery and fostering greater public trust in the legal system. This study underscores the need for robust legal reform to strengthen the eradication of corruption and uphold justice.